The Correlation of AI Literacy and Writing Skill on 11th Senior High Students in Denpasar - I Kadek Wahyu Widana; Made Hery Santosa; I Putu Indra Kusuma (Universitas Islam Negeri Palopo, 2025)
This research analyzed the correlation of AI literacy and writing of senior high students in Harapan Senior High School on South Denpasar, Bali. This research analyzed the correlation and the strength level of relationship between AI literacy and writing skills. The correlational study design had been utilized as the research design. This study utilized the purposive sampling technique and found out from 227 senior high school students with 151 participated in this study. The data collection used in this study was survey questionnaires, which had 22 questions in total. This research found out that there was a positive and significant correlation between AI literacy and writing skill of the students (Sig. 2-tailed result < 0.05). Also, this study found out that the strength level of relationship between AI literacy and writing skill reached Moderate Positive relationship (Pearson correlation coefficient (r) 0.366, and the p-value 0.001 < 0.05). The results showed that as the students’ AI literacy got better, their writing skill also improved together. Since the positive and significant correlation between AI literacy and writing skill, means the students’ writing skill development could also be improved along with their AI literacy since they correlated each other. This research also suggested the need of AI literacy improvement towards the students when the AI tools were implemented into the English learning process, and further research about the other English language skill fields that relates with the AI literacy. That way, the finding of this study suggested the empirical implications towards the teachers that the implementation and improvement of AI tools into English learning process had to be focused on the students’ AI literacy as well. It could lead to students’ comprehension towards the AI tools itself since they had understood the basic literacy of AI.